Case report: Anti N-methyl-D-aspartate autoimmune encephalitis following a mildly symptomatic COVID-19 infection in an adolescent male - Hainmueller, Thomas; Lewis, Lambert; Furer, Tzvi (Frontiers in Psychiatry, 2023)
Background Antibodies against N-methyl-D-aspartate receptors are the most commonly identified cause of autoimmune encephalitis. While predominantly associated with malignancies, cases of anti-N-methyl-D-aspartate receptor autoimmune encephalitis have been reported after infections with the herpes-simplex virus or, more recently, in patients with severe COVID-19 disease. Case presentation A previously healthy 17-year-old male adolescent acutely developed psychosis with auditory and visual hallucinations, fluctuating mental status, and an isolated seizure 5 weeks after a mildly symptomatic COVID-19 infection. The symptoms continued to worsen, accompanied by catatonia, and additional neurological symptoms developed during the initial antipsychotic treatment. A diagnostic workup revealed antibodies against N-methyl-D-aspartate receptors in the cerebrospinal fluid without other major abnormalities. After establishing the diagnosis, initiation of immunomodulatory therapy stopped the symptom progression and led to full recovery within 2 months. Conclusion The case is remarkable in that anti-N-methyl-D-aspartate receptor autoimmune encephalitis developed shortly after a COVID-19 infection in an adolescent, despite the individual experiencing only mild COVID symptoms. The diagnosis should be considered in cases of acute-onset psychotic symptoms during or after COVID-19 infection, particularly in individuals without a prior psychiatric history, who present with atypical psychiatric or neurological features.